Volume 5B: 39th Mechanisms and Robotics Conference 2015
DOI: 10.1115/detc2015-46670
|View full text |Cite
|
Sign up to set email alerts
|

Designing Variable-Geometry Extrusion Dies That Utilize Planar Shape-Changing Rigid-Body Mechanisms

Abstract: This paper presents a kinematic synthesis methodology for planar shape-changing rigid-body mechanisms that addresses constraints arising in the design of variable-geometry polymer extrusion dies. Such a die is capable of morphing its orifice in order to create extrusions of non-constant cross section. A variable-geometry shape-changing die problem is defined by a set of design profiles of different shapes and arc lengths, which approximate various cross sections of the extrusion. The primary advantage of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A true variable-geometry die might have an integrated actuator that could adjust the die dimensions in real time during the extrusion process to produce distributionready products more quickly. Some work has been done in designing [9] and prototyping [10] such dies, though these existing variable-geometry dies lack integrated actuation and control.…”
Section: Introductionmentioning
confidence: 99%
“…A true variable-geometry die might have an integrated actuator that could adjust the die dimensions in real time during the extrusion process to produce distributionready products more quickly. Some work has been done in designing [9] and prototyping [10] such dies, though these existing variable-geometry dies lack integrated actuation and control.…”
Section: Introductionmentioning
confidence: 99%
“…Concepts for variable-geometry die design have shown that revolute joints are difficult to implement, whereas prismatic joints (straight or curved) have fewer mechanical design challenges [10]. To accommodate die design, shape-changing mechanism theory is extended to produce designs that place a priority on prismatic joints and to eliminate or reduce revolute joints [15]. This paper provides techniques for the design of variablegeometry, polymer extrusion dies including desirable design features and the methodology for synthesizing links that match desired exit profiles.…”
Section: Introductionmentioning
confidence: 99%